2019
DOI: 10.1021/acs.est.9b04274
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive Deionization of Saline Water by Using MoS2–Graphene Hybrid Electrodes with High Volumetric Adsorption Capacity

Abstract: Capacitive deionization (CDI) has received wide attention as an emerging water treatment technology because of its low energy consumption, low cost, and high efficiency. However, the conventional carbon electrode materials for CDI have low densities, which occupy large volumes and are disadvantageous for use in limited space (e.g., in household or on offshore platforms). In order to miniaturize the CDI device, it is quite urgent to develop high volumetric adsorption capacity (VAC) electrode materials. To overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(66 citation statements)
references
References 61 publications
(85 reference statements)
0
52
1
Order By: Relevance
“…Carbonaceous adsorbents 39,40,[44][45][46] (e.g., activated carbon, graphene, carbon nanotubes) are attractive due to their chemical durability and thermal stability, 47 and a large specic surface area that can accelerate the adsorption kinetics. 48 However, most carbonaceous adsorbents exhibit a relatively low adsorption capacity (i.e., the amount of contaminant taken up by the unit mass of adsorbent) 49 for PFAS with a short uoroalkyl chain length. [50][51][52][53][54] Further, these absorbents oen suffer from a decrease in the adsorption capacity over time because the residual PFAS remains even aer the regeneration process.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonaceous adsorbents 39,40,[44][45][46] (e.g., activated carbon, graphene, carbon nanotubes) are attractive due to their chemical durability and thermal stability, 47 and a large specic surface area that can accelerate the adsorption kinetics. 48 However, most carbonaceous adsorbents exhibit a relatively low adsorption capacity (i.e., the amount of contaminant taken up by the unit mass of adsorbent) 49 for PFAS with a short uoroalkyl chain length. [50][51][52][53][54] Further, these absorbents oen suffer from a decrease in the adsorption capacity over time because the residual PFAS remains even aer the regeneration process.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, graphene is considered an important material in wastewater treatment technologies because of its outstanding features 3 , 21 , 22 . Up to now, graphene and its derivatives are used as a matrix of metal/metal oxide materials to enhance the catalytic performance of materials, including Ni 19 –NiO 23 for dye-synthesized solar cell, CuO 24 for catalysts, Pd–Ag 25 and AuNPs/MoS 2 26 for the electrochemical sensor, TiO 2 27 and MoS 2 28 for electrode, AgBr 29 and Fe 3 O 4 30 for water purification, or water splitting 19 . Yuan et al suggested a new mechanism for the improvement of photocatalytic activities with graphene.…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 as CDI electrode cannot give a satisfactory performance, possibly due to the poor conductivity and low accessible active sites. Shortly afterward, various low dimensional nanomaterials such as CNT (Srimuk et al, 2017), graphene (Han J. L. et al, 2019;Peng et al, 2020), or g-C 3 N 4 (Tian et al, 2020) were employed to further improve the performance of MoS 2 .…”
Section: Faradaic Materialsmentioning
confidence: 99%